A simulation model to predict the most efficient way to utilise operational resources when vaccinating badgers against bTB - Richard Budgey; Megan Bird (PLoS ONE, 2026)
Bovine tuberculosis (bTB) is a disease carried by badgers that seriously impacts the health and productivity of cattle in the United Kingdom (UK). The UK government’s aim is to be officially TB-free in cattle by 2038 in England and badger vaccination is one approach that can be used to achieve this. We use a simulation model to compare the relative performance of different vaccination strategies (treatment every year, every second year and every third year) under different field conditions and assumptions about vaccine efficacy. Population density, disease prevalence and duration of vaccine-induced immunity substantially affected the outcome of vaccination. A vaccine strategy with lower frequency treatment was effective and offers operational efficiency as multiple areas can be treated near concurrently by a single vaccination team, potentially halving the cost per unit area. The information presented here may be used to guide operational managers and decision makers towards a more efficient strategy in a particular area and may provide an estimation of the likely success of the chosen strategy.